PENGARUH DISIPLIN DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN PADA PT KORIN TECHNOMIC KABUPATEN TANGERANG - Durotun Napisoh, Ayu; Wiguna, Melda (Journal of Research and Publication Innovation, 2024)
The aim of this research is to determine the influence of discipline and work environment on employee performance at PT Korin Technomic Tangerang. This research method uses quantitative methods. The population in this study was all 55 employees of PT Korin Technomic. This sampling technique uses saturated samples with a sample size of 55 people. The data analysis method in this research uses the SPSS IBM Version 26 application. Includes validity test, reliability test, classical assumption test, multiple linear regression test, multiple coefficient test, t test and f test. The results of this research are that discipline has a significant effect on employee performance (Y) with a determination value of 36.7% and in hypothesis testing the calculated t value > t table or 5.549 > 2.006 with a significant value of 0.000 < 0.05. Work Environment (X2) has a significant effect on Employee Performance (Y) with a determination value of 51.5% and in the hypothesis test the calculated t value < t table or 7.496 < 2.006 with a significant value of 0.000 < 0.05. Discipline (X1) and work environment (X2) simultaneously have a significant effect on employee performance (Y) with the regression equation Y = 4.537 + 0.318 X1 + 0.580 X2. The coefficient of determination value is 60.3%. Hypothesis testing obtained a calculated F value > F table or 39.521 > 3.172. This is also reinforced by a significant value of 0.000 < 0.05. Thus, H0 is rejected and Ha is accepted. This shows that there is a significant simultaneous influence between discipline and the work environment on employee performance at PT Korin Technomic Tangerang.